2020
DOI: 10.1007/s10570-020-03245-z
|View full text |Cite
|
Sign up to set email alerts
|

Modification of softwood kraft pulp fibres using hydrogen peroxide at acidic conditions

Abstract: The aim of this work was to provide softwood kraft pulp fibres with new functionalities by the introduction of carbonyl groups. Carbonyl groups are known to affect properties such as wet strength through the formation of covalent bonds, i.e. hemiacetals. The method developed involves oxidation using hydrogen peroxide at mildly acidic conditions. It was found that the carbonyl group content increased with both increasing temperature and residence time when oxidized at acidic conditions. The number of carboxylic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Temperatures varied between 65 and 85°C and residence times varied between 30 and 90 minutes. The results were compared to previous results obtained from oxidations of softwood pulp (Martinsson et al 2020). The rate of oxidation is fairly low below 85°C, which makes comparison difficult: comparisons with softwood pulp were therefore only made at 85°C.…”
Section: Acidic Oxidation Of Hardwood Pulpmentioning
confidence: 89%
See 1 more Smart Citation
“…Temperatures varied between 65 and 85°C and residence times varied between 30 and 90 minutes. The results were compared to previous results obtained from oxidations of softwood pulp (Martinsson et al 2020). The rate of oxidation is fairly low below 85°C, which makes comparison difficult: comparisons with softwood pulp were therefore only made at 85°C.…”
Section: Acidic Oxidation Of Hardwood Pulpmentioning
confidence: 89%
“…Previous work (Martinsson et al 2020) has shown that the oxidation of softwood pulp using hydrogen peroxide at acidic conditions led to an increase in the formation of carbonyl groups. The utilization of a common bleaching agent, such as hydrogen peroxide, to introduce carbonyl groups could potentially open up for the large-scale production of a pulp with inherent wet-strength, without the need for the further addition of wet-strength agents, in some applications.…”
Section: Introductionmentioning
confidence: 97%
“…It is becoming apparent that NaBH4 is increasingly being used as a reducing agent in multi-stage bleaching. NaBH4 reduces carbonyl groups to alcohol groups and improves reflectivity over a wider range than sodium or zinc hydrosulfite (Çiçekler et al, 2022;Ferrandin-Schoffel et al, 2023;Martinsson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%